2018
DOI: 10.1507/endocrj.ej18-0026
|View full text |Cite
|
Sign up to set email alerts
|

The roles of kisspeptin and gonadotropin inhibitory hormone in stress-induced reproductive disorders

Abstract: Abstract. Several kinds of stress suppress the hypothalamic-pituitary-gonadal (HPG) axis and reproductive behavior in humans and animals. These changes can eventually cause diseases and disorders, such as amenorrhea and infertility. In previous studies, it has been shown that stress-related factors, e.g., corticotropin-releasing hormone, cortisol, and proinflammatory cytokines, promote the stress-induced suppression of the HPG axis. However, these mechanisms are not sufficient to explain how stress suppresses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 91 publications
0
22
0
Order By: Relevance
“…Neuroendocrine sex differences in regulation of eating behavior have been thoroughly reviewed (110, 111). Recently discovered hypothalamic peptides kisspeptin, gonadatropin-inhibitory peptide and amide-related peptide-3 all seem to be involved in the genesis of stress-induced hypothalamic amenorrhea (112), but their potential role in AN remains uncertain.…”
Section: Hypothalamic–pituitary–gonadal Axismentioning
confidence: 99%
“…Neuroendocrine sex differences in regulation of eating behavior have been thoroughly reviewed (110, 111). Recently discovered hypothalamic peptides kisspeptin, gonadatropin-inhibitory peptide and amide-related peptide-3 all seem to be involved in the genesis of stress-induced hypothalamic amenorrhea (112), but their potential role in AN remains uncertain.…”
Section: Hypothalamic–pituitary–gonadal Axismentioning
confidence: 99%
“…Moreover, some studies have suggested a positive correlation between kisspeptin and LH secretory pulses [ 10 ]. Kisspeptin may also influence the negative and positive feedback of estrogen [ 11 ]. Many reports have emphasized the sensitivity of kisspeptin to the metabolic state of the body and to stress, both acute and chronic [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kisspeptin may also influence the negative and positive feedback of estrogen [ 11 ]. Many reports have emphasized the sensitivity of kisspeptin to the metabolic state of the body and to stress, both acute and chronic [ 10 , 11 ]. It was reported that the higher the cortisol level is, the lower the plasma level of kisspeptin will be [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…[18, 27, 29]. Growing evidence indicated that gonadotropin inhibitory hormone (GnIH) also play pivotal roles in the stress-induced disruption of the hypothalamus-pituitary-gonadal axis [5, 12].…”
Section: Discussionmentioning
confidence: 99%